2017
DOI: 10.1186/s12915-017-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear genetic codes with a different meaning of the UAG and the UAA codon

Abstract: BackgroundDepartures from the standard genetic code in eukaryotic nuclear genomes are known for only a handful of lineages and only a few genetic code variants seem to exist outside the ciliates, the most creative group in this regard. Most frequent code modifications entail reassignment of the UAG and UAA codons, with evidence for at least 13 independent cases of a coordinated change in the meaning of both codons. However, no change affecting each of the two codons separately has been documented, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…The canonical genetic code has three stop codons (UAA, UAG, and UGA), and the efficiency of termination is enhanced by a purine residue in the +4 position and by a +5 purine if the +4 residue is a pyrimidine (McCaughan et al 1995). In a few organisms, including some ciliate protists, green algae, and diplomonads, UGA is reassigned as a sense codon and UAA and UAG are retained as stop codons, UAA and UAG are reassigned as sense codons with UGA as the sole termination codon, or UAG is reassigned as a sense codon and UAA and UGA function as stop codons (Keeling 2016;Pánek et al 2017).…”
Section: Stop Codon Recognitionmentioning
confidence: 99%
“…The canonical genetic code has three stop codons (UAA, UAG, and UGA), and the efficiency of termination is enhanced by a purine residue in the +4 position and by a +5 purine if the +4 residue is a pyrimidine (McCaughan et al 1995). In a few organisms, including some ciliate protists, green algae, and diplomonads, UGA is reassigned as a sense codon and UAA and UAG are retained as stop codons, UAA and UAG are reassigned as sense codons with UGA as the sole termination codon, or UAG is reassigned as a sense codon and UAA and UGA function as stop codons (Keeling 2016;Pánek et al 2017).…”
Section: Stop Codon Recognitionmentioning
confidence: 99%
“…Given the vast amount of new genomic and metagenomic DNA sequence information generated in the past few years, we document here the current knowledge of natural deviations from the standard genetic code (45, 61, 79, 92, 94, 98, 115, 125, 134, 157) (Figure 2) (Supplemental Figure 1). Previously, it was well known that Candida yeast reassigns the CUG codon from leucine (Leu) to serine (Ser) (60) and that many ciliates reassign either the UGA stop codon or both the UAA and the UAG stop codons to a canonical amino acid (12, 61, 88, 119) (Figure 2).…”
Section: Natural Expansion Of the Genetic Codementioning
confidence: 99%
“…Recent eukaryotic genome/transcriptome analyses identified that ( a ) Pachysolen tannophilus , a yeast species distinct from Candida spp., reassigns CUG to alanine (Ala; 92, 125) (Figure 2); ( b ) diverse single-celled eukaryotes that are nonciliate also reassign stop codons to amino acids (17, 19, 59, 62, 63, 115, 157) (Figure 2); ( c ) not only Gln but also Leu, tyrosine (Tyr), and glutamic acid (Glu) are assigned to UAR [R denotes adenosine (A) and guanine (G)] (45, 134) or to UAG (115) (Figure 2); and ( d ) ciliates Parduczia sp. and Condylostoma magnum and trypanosomatids Blastocrithidia spp.…”
Section: Natural Expansion Of the Genetic Codementioning
confidence: 99%
“…Changes in sensory perception or other neural systems must underlie differences in innate behaviours between species, and will ultimately have a genetic basis. Although the significance of behavioural barriers for speciation has been recognized since the Modern Synthesis 3 , we know little of the genes underlying changes in mating preferences, or variation in behaviours across natural populations more broadly 4 . Identifying these genes will provide an important route towards understanding how behavioural differences are generated, both during development and across evolutionary time.…”
Section: Introductionmentioning
confidence: 99%